Effects of Evolocumab on Vitamin E and Steroid Hormone Levels. Issue 8 (25th September 2015) - Blom, Dirk J.; Djedjos, C. Stephen; Monsalvo, Maria Laura; Bridges, Ian; Wasserman, Scott M.; Scott, Rob; Roth, Eli
<x xml:space="preserve">Abstract</x> Rationale: Vitamin E transport and steroidogenesis are closely associated with low-density lipoproteins (LDLs) metabolism, and evolocumab can lower LDL cholesterol (LDL-C) to low levels. Objective: To determine the effects of evolocumab on vitamin E and steroid hormone levels. Methods and Results: After titration of background lipid-lowering therapy per cardiovascular risk, 901 patients with an LDL-C ≥2.0 mmol/L were randomized to 52 weeks of monthly, subcutaneous evolocumab, or placebo. Vitamin E, cortisol, adrenocorticotropic hormone, and gonadal hormones were analyzed at baseline and week 52. In a substudy (n=100), vitamin E levels were also measured in serum, LDL, high-density lipoprotein, and red blood cell membranes at baseline and week 52. Absolute vitamin E decreased in evolocumab-treated patients from baseline to week 52 by 16% but increased by 19% when normalized for cholesterol. In the substudy, vitamin E level changes from baseline to week 52 mirrored the changes in the lipid fraction, and red blood cell membrane vitamin E levels did not change. Cortisol in evolocumab-treated patients increased slightly from baseline to week 52, but adrenocorticotropic hormone and the cortisol:adrenocorticotropic hormone ratio did not change. No patient had a cortisol:adrenocorticotropic hormone ratio <3.0 (nmol/pmol). Among evolocumab-treated patients, gonadal hormones did not change from baseline to week 52. Vitamin E and steroid changes were consistent across subgroups by minimum postbaseline LDL-C <0.4 and <0.6 mmol/L. Conclusions: As expected, vitamin E levels changed similarly to lipids among patients treated for 52 weeks with evolocumab. No adverse effects were observed in steroid or gonadal hormones, even at very low LDL-C levels. Clinical Trial Registration: URL: http://www.clinicaltrials.gov. Unique identifier: NCT01516879.